Light in architecture - Uffelen, Chris van. (: Braun Publish,Csi, 2012)
Light is the prerequisite for spatial perception, which is why it is an integral component of architecture. Light design in architecture has become more lively and also more colourful in the last few years. The projects selected here show how good architecture is improved with the right light. With interior design, the purpose of the introduction of natural light and the use of artificial light is to create a spatial experience: certain areas are accentuated, spatial units are defined and differing atmospheres are established. Illumination also plays a role with exteriors, not just at night. In addition to the form emphasizing role of light, a striking illumination can lend the building an emblematic uniqueness.
Keywords: Light in architecture; Lighting, Architectural and decorative